2008
DOI: 10.1016/j.cub.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Abi Mutants in Dictyostelium Reveal Specific Roles for the SCAR/WAVE Complex in Cytokinesis

Abstract: Actin polymerization drives multiple cell processes involving movement and shape change. SCAR/WAVE proteins connect signaling to actin polymerization through the activation of the Arp2/3 complex. SCAR/WAVE is normally found in a complex with four other proteins: PIR121, Nap1, Abi2,and HSPC300 (Figure S1A available online) [1-3]. However,there is no consensus as to whether the complex functions as an unchanging unit or if it alters its composition in response to stimulation, as originally proposed by Edenet al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…In addition to these structural roles, WASPfamily proteins have central roles in membrane trafficking, and are manipulated during infection by intracellular pathogens. Other emerging roles include cell-substrate adhesion (Ibarra et al, 2006) and cytokinesis (Pollitt and Insall, 2008); others will no doubt continue to emerge.…”
Section: Biological Functions Of Waspfamily Proteinsmentioning
confidence: 99%
“…In addition to these structural roles, WASPfamily proteins have central roles in membrane trafficking, and are manipulated during infection by intracellular pathogens. Other emerging roles include cell-substrate adhesion (Ibarra et al, 2006) and cytokinesis (Pollitt and Insall, 2008); others will no doubt continue to emerge.…”
Section: Biological Functions Of Waspfamily Proteinsmentioning
confidence: 99%
“…Previous work has shown that in Dictyostelium, misregulation of the SCAR complex by disruption of the Abi subunit leads to aberrant mitosis (Pollitt and Insall, 2008). The only in vivo assay for SCAR activity is to image the localisation of the complex, which coincides with areas of polymerised actin (Weiner et al, 2007).…”
Section: Enhanced Migration and Activation Of Scar At Cytokinesismentioning
confidence: 99%
“…SCAR function is not essential for Dictyostelium cytokinesis (Blagg et al, 2003), but disruption of the Abi subunit of the complex leads to inappropriate SCAR activation (Pollitt and Insall, 2008), which can disrupt normal cell division. Consistent with this, others showed that cells overexpressing an N-terminal truncation of SCAR also rapidly become multinucleate (Caracino et al, 2007) indicating that SCAR activity must be tightly regulated for normal cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…Abi2-KO mice exhibit a severe memory loss thought to be caused by deficiencies in dendritic spine and adherens junction formation and abnormal cell-cell communication (27). A role for Abi in regulation of the cytoskeleton and in cytokinesis has been confirmed in Dictyostelium (28). Dictyostelium has only one Abi gene; thus it offers no specific conclusion for roles of mammalian Abi1 or Abi2.…”
mentioning
confidence: 99%